LANGUAGE ANALYSIS IN PROMOTION OF BEAUTY PRODUCTS ON SHOPEE IN SKINTIFIC ACCOUNT - Abrar, Virza Ananda; Wahyudi, Athalla Ahmad Dias; Fadiansah, Nailah Ramadhani; Br Ginting, Salsalina Aprilia; Nurhayati, Eni (Universitas Muhammadiyah Tangerang, 2024)
This research is entitled